Acute Unilateral Audiovestibulopathy due to Embolic Labyrinthine Infarction - Liqun, Zhong; Park, Kee-Hong; Kim, Hyo-Jung; Lee, Sun-Uk; Choi, Jeong-Yoon; Kim, Ji-Soo (Frontiers in Neurology, 2018)
Introduction: Labyrinthine infarction is a cause of acute audiovestibulopathy, but can be diagnosed only in association with other infarctions involving the brainstem or cerebellar areas supplied by the anterior inferior cerebellar artery (AICA) since current imaging techniques cannot visualize an infarction confined to the labyrinth. This case series aimed to establish embolic labyrinthine infarction as a mechanism of isolated acute audiovestibulopathy. Methods: We analyzed clinical features, imaging findings, and mechanisms of embolism in 10 patients (8 men, age range: 38-76) who had developed acute audiovestibulopathy in association with an obvious source of embolism and concurrent acute embolic infarctions in the non-AICA territories. The presence of audiovestibulopathy was defined when bedside or laboratory evaluation documented unilateral vestibular (head impulse tests or caloric tests) or auditory loss (audiometry). Results: Six patients showed combined audiovestibulopathy while three had isolated vestibulopathy. One patient presented isolated hearing loss. Audiovestibular findings were the only abnormalities observed in nine patients. In all patients, MRIs documented single or multiple infarctions in the cerebellum (n=5) or cerebral hemispheres (n=5). Especially 3 patients showed single or scattered foci of tiny acute infarctions only in the cerebral hemispheres. Cardiac sources of embolism were found in eight, and artery-to-artery embolism was presumed in two patients. Conclusion: Selective embolism to the labyrinth may be considered in patients with acute unilateral audiovestibulopathy and concurrent acute infarctions in the non-AICA territories.